Effect of compost application on soil fertility parameters and productivity of cocoa (Theobroma cacao L.). Issue 4 (July 2021) - Muthmainnah,; Padjung, R; Nasaruddin,; Asrul, L; Kurniawan,; Setiani, UE
Abstract: Cocoa is one of the plantation crops that has an important role in the national economy, yet its production has decreased due to ineffective plants' treatment. One thing that can be done to solve this problem is applying organic material by effectively applying compost. This study aims to determine cocoa husk compost application on soil fertility and cocoa plant productivity. This research was conducted in Gantarangkeke Village, Gantarangkeke District, Bantaeng Regency, South Sulawesi Province, and took place from March to September 2020. This study used a randomized block design (RBD) as its environmental design. Compost application consists of 5 levels, namely control (0 kg/tree), (2.5 kg/tree), (5 kg/tree), (7.5 kg/tree), (10 kg/tree). The results of the research experiment showed that compost application of 10 kg/tree resulted in a pH of 6.3, CEC value of 27.14 cmol (+) kg −1, organic C content of 2.16%, available P content of 18.1 ppm, K content of 0.46 cmol (+) kg −1, Number of fruit/tree of 9.67 (fruit), number of seeds/fruit of 28.37 (seeds), the weight of 100 dry seeds of 113.17 (g), dry seeds per tree of 315.50 (g), and dry seeds per hectare of 350.50 (kg/ha). Compost application with several different doses had a significant effect on cocoa's growth and production, especially at a dose of 10 kg/tree.